Does environmental regulation dividends inequality impact inclusive growth? Evidence from China - Ge, Tao; Ding, Ziqi; Lin, Shuowan; Yang, Yumeng; Ji, Jianhua (Frontiers in Public Health, 2022)
Based on the panel data of 281 city level in China for the period of 2004–2016, this study uses the Cobb–Douglas production function to investigate the distribution of environmental regulation dividends and further adopts the threshold model to explore the impact of environmental regulation dividends inequality (ERDI) on inclusive growth (IG). Results indicate that the distribution structure of the environmental regulation dividends has improved, but the inequality between urban–rural residents is still apparent. Environmental regulation dividends inequality has a non-linear threshold effect on inclusive growth, which turns from a significant inhibition to a slight promotion after exceeding the threshold value. Grouping tests show that environmental regulation dividends inequality has a heterogeneous effect on cities with different resource endowments and leading industries and still inhibits inclusive growth of non-resource-based cities even if the inequality is higher than the threshold value. Mechanism analysis reveals that primary distribution and redistribution are the main channels through which environmental regulation dividends inequality inhibits and promotes inclusive growth when the inequality is below and above the threshold value, respectively. These conclusions have important implications for enhancing and distributing environmental regulation dividends to promote inclusive growth.